2022
DOI: 10.7554/elife.77779
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of the human ESCRT-III-MIT domain interactome reveals new cofactors for cytokinetic abscission

Abstract: The 12 related human ESCRT-III proteins form filaments that constrict membranes and mediate fission, including during cytokinetic abscission. The C-terminal tails of polymerized ESCRT-III subunits also bind proteins that contain Microtubule-Interacting and Trafficking (MIT) domains. MIT domains can interact with ESCRT-III tails in many different ways to create a complex binding code that is used to recruit essential cofactors to sites of ESCRT activity. Here, we have comprehensively and quantitatively mapped t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
59
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(67 citation statements)
references
References 158 publications
(326 reference statements)
6
59
2
Order By: Relevance
“…The tandem CAPN7 MIT domains (CAPN7(MIT) 2 ) bind a C-terminal region of IST1 that contains two distinct MIM elements (Figure 1A) (Agromayor et al ., 2009; Bajorek et al ., 2009; Osako et al ., 2010; Wenzel et al ., 2022). We quantified this interaction using fluorescence polarization anisotropy binding assays with purified, recombinant CAPN7(MIT) 2 and fluorescently labeled IST constructs that spanned either one or both of the MIM elements.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The tandem CAPN7 MIT domains (CAPN7(MIT) 2 ) bind a C-terminal region of IST1 that contains two distinct MIM elements (Figure 1A) (Agromayor et al ., 2009; Bajorek et al ., 2009; Osako et al ., 2010; Wenzel et al ., 2022). We quantified this interaction using fluorescence polarization anisotropy binding assays with purified, recombinant CAPN7(MIT) 2 and fluorescently labeled IST constructs that spanned either one or both of the MIM elements.…”
Section: Resultsmentioning
confidence: 99%
“…We quantified this interaction using fluorescence polarization anisotropy binding assays with purified, recombinant CAPN7(MIT) 2 and fluorescently labeled IST constructs that spanned either one or both of the MIM elements. These experiments showed that both IST1 MIMs contribute to binding (Figure 1B) (Osako et al ., 2010, Wenzel et al ., 2022). The double MIM IST1 316-366 construct bound CAPN7(MIT) 2 tightly (K D = 0.09 ± 0.01 µM), and the first IST1 MIM element (IST1 344-366 ) contributed most of the binding energy (K D = 1.8 ± 0.1 µM).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations